2020
DOI: 10.1177/1938965520909094
|View full text |Cite
|
Sign up to set email alerts
|

Paranormal Tourism: Market Study of a Novel and Interactive Approach to Space Activation and Monetization

Abstract: We review the premise, popularity, and profitability of paranormal tourism, which involves visits to any setting or locale for the explicit purpose of encountering apparent supernatural phenomena for leisure, investigation, services, products, or conventions. This niche sector can offer an inherently engaging conceptual framework for seasonal or year-round space activation and monetization by businesses situated in specific settings or cities. On a broader level, the niche also illustrates how tourism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 80 publications
(65 reference statements)
3
34
0
Order By: Relevance
“…This holistic view identifies psychosocial elements as important contributors to the onset or structure of personal experiences, which agrees with conclusions from our broad sociocultural analyses of ghost narratives (Hill et al, 2018(Hill et al, , 2019Drinkwater et al, 2019;Houran et al, 2020). To be sure, considerable evidence implicates attitudinal, normative, and situational influences in the phenomenology of witness accounts (Houran, 2002;Houran et al, 2002bHouran et al, , 2019aWiseman et al, 2002Wiseman et al, , 2003bFrench et al, 2009;Drinkwater et al, 2013Drinkwater et al, , 2017Dagnall et al, 2015a;Laythe et al, 2018;Pharino et al, 2018;Langston and Hubbard, 2019).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This holistic view identifies psychosocial elements as important contributors to the onset or structure of personal experiences, which agrees with conclusions from our broad sociocultural analyses of ghost narratives (Hill et al, 2018(Hill et al, , 2019Drinkwater et al, 2019;Houran et al, 2020). To be sure, considerable evidence implicates attitudinal, normative, and situational influences in the phenomenology of witness accounts (Houran, 2002;Houran et al, 2002bHouran et al, , 2019aWiseman et al, 2002Wiseman et al, , 2003bFrench et al, 2009;Drinkwater et al, 2013Drinkwater et al, , 2017Dagnall et al, 2015a;Laythe et al, 2018;Pharino et al, 2018;Langston and Hubbard, 2019).…”
Section: Discussionsupporting
confidence: 87%
“…In fact, houses rumored to be haunted often suffer significant value diminution, and this is especially true in countries such as Taiwan and Hong Kong (China) where haunts have strong cultural associations with bad luck, vengeful ghosts, and ancestral spirit anger (Emmons, 1982;Chu, 2016;Bhattacharya et al, 2017). On the other hand, "haunted" buildings or sites in Western culture are often promoted favorably as tourist destinations (Hanks, 2015;Houran et al, 2020). Sales of these places can bring high prices if a paranormal reputation is regarded as a benefit by buyers (Behar, 2017).…”
Section: Possibly Morementioning
confidence: 99%
See 1 more Smart Citation
“…This is essentially the heart of the well-substantiated Thomas Theorem (Merton, 1995)-that which is perceived as real will be real in its consequences. Sociocultural analyses demonstrate that ghostly episodes are no exception to these tenets (Drinkwater et al, 2019;Hill et al, 2018Hill et al, , 2019Houran et al, 2020). Part of basic human psychology lies in confirming personal beliefs and predictions of the world to provide control (Langer & Rodin, 1976), which to some extent, maintains one's self-esteem or well-being (Tajfel & Turner, 1986).…”
Section: Additional Influences On Psychological Set and Concomitant Phenomenologymentioning
confidence: 99%
“…The study that was carried out showed that many places in Córdoba are feasible for implementing so-called dark tourism, especially ghost activities, and routes can be linked between municipalities, which allows for experiential tourism because paranormal experiences are very special occurrences that transport consumers to “otherworldly” destinations and make for unforgettable, unfamiliar, and supremely shareable memories and stories [ 53 ].…”
Section: Discussionmentioning
confidence: 99%